Pengaruh Latihan Plyometrics terhadap Ketepatan Shooting dalam Permainan Futsal pada Peserta Eksrtakurikuler di SMP Negeri 35 Palembang - Ari Prayoga Mukti; Agung Mahendra; Rury Rizhardi (Departement of Mathematics Education, 2023)
The researcher aims to determine whether there is an effect of plyometrics training on shooting accuracy in futsal games. The problem in this study is whether there is an effect of plyometrics training on shooting accuracy in futsal games for extracurricular participants at SMP Negeri 35 Palembang. The method used in this study using the experimental method. The types of research used in this study were pretest, treatment and posttest where all participants were given plyometrics training. The sample in this study were 20 extracurricular participants at SMP Negeri 35 Palembang. Based on the data from the initial test (pretest) and posttest (posttest), the shooting accuracy showed that the results of the initial test obtained the lowest score of 18 and the highest score of 34, after being treated for 5 weeks the participants experienced an increase in the lowest score of 28 and the highest score of 48. It turns out that there is an effect of plyometrics training on shooting accuracy in futsal games for extracurricular participants at SMP Negeri 35 Palembang. From the results of the analysis using statistical tests, it can be concluded that tcount is 14.038 ttable is 2.093, so reject Ho and accept Ha means,